New to the board : a case study of Canadian tire corporation and the potential purchase of the Forzani Group Limited - Naraine, Michael L.; Dixon, Jess C.; Horton, Candice (London : Human Kinetics, Inc., 2015)
This case study explores the potential purchase of the Forzani Group Limited by the Canadian Tire Corporation. Students take on the role of Sara Brown, a new member of Canadian Tire's board of directors. With an emergency meeting scheduled for the following morning to decide the fate of the proposed acquisition, Brown has been called upon to provide input to the board given her aptitude for corporate acquisitions and mergers. The case profiles both companies and details the state of the retail sport industry in Canada. Notably, there is emphasis on company product offerings (e.g., merchandise), financials (e.g., balance sheets), and goodwill (e.g., charities) to provide students with pertinent information to develop their argument(s) for and/or against the acquisition. Primary learning objectives include engaging in environmental scanning exercises (e.g., SWOT analyses) and evaluating market forces present in the retail sporting goods industry.
Originally published in Naraine, M. L., Dixon, J. C., & Horton, C. (2015). New to the board: A case study of Canadian Tire Corporation and the potential purchase of the Forzani Group Limited. Case Studies in Sport Management, 4(1), 120-131. DOI:.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Canadian Tire Corporation -- Case studies; Consolidation and merger of corporations -- Case studies